On the mechanism of piezoresistance in nanocrystalline graphite - Kumar, Sandeep; Dehm, Simone; Krupke, Ralph (Beilstein Journal of Nanotechnology, 2024)
Strain sensors are sensitive to mechanical deformations and enable the detection of strain also within integrated electronics. For flexible displays, the use of a seamlessly integrated strain sensor would be beneficial, and graphene is already in use as a transparent and flexible conductor. However, graphene intrinsically lacks a strong response, and only by engineering defects, such as grain boundaries, one can induce piezoresistivity. Nanocrystalline graphene (NCG), a derivative form of graphene, exhibits a high density of defects in the form of grain boundaries. It holds an advantage over graphene in easily achieving wafer-scale growth with controlled thickness. In this study, we explore the piezoresistivity in thin films of nanocrystalline graphite. Simultaneous measurements of sheet resistance and externally applied strain on NCG placed on polyethylene terephthalate (PET) substrates provide intriguing insights into the underlying mechanism. Raman measurements, in conjunction with strain applied to NCG grown on flexible glass, indicate that the strain is concentrated at the grain boundaries for smaller strain values. For larger strains, mechanisms such as grain rotation and the formation of nanocracks might contribute to the piezoresistive behavior in nanocrystalline graphene.
Keywords: grain boundary; nanocrystalline graphene; strain sensor; Raman; tunneling and destruction